Association of enteric parasitic infections with intestinal inflammation and permeability in asymptomatic infants of São Tomé Island. (3rd April 2017) - Garzón, Marisol; Pereira-da-Silva, Luis; Seixas, Jorge; Papoila, Ana Luísa; Alves, Marta; Ferreira, Filipa; Reis, Ana
Abstract: The cumulative effect of repeated asymptomatic enteric infections on intestinal barrier is not fully understood in infants. We aimed to evaluate the association between previous enteric parasitic infections and intestinal inflammation and permeability at 24-months of age, in asymptomatic infants of São Tomé Island. A subset of infants from a birth cohort, with intestinal parasite evaluations in at least four points of assessment, was eligible. Intestinal inflammatory response and permeability were assessed using fecal S100A12 and alpha-1-antitrypsin (A1AT), respectively. The cutoff <–1SD for weight-for-length and length-for-age was used to define wasting and stunting. Multivariable linear regression analysis explored if cumulative enteric parasitic infections explained variability of fecal biomarkers, after adjusting for potential confounders. Eighty infants were included. Giardia duodenalis and soil-transmitted helminths (STH) were the most frequent parasites. The median (interquartile range) levels were 2.87 μg/g (2.41–3.92) for S100A12 and 165.1 μg/g (66.0–275.6) for A1AT. Weak evidence of association was found between S100A12 levels and G. duodenalis ( p = 0.080) and STH infections ( p = 0.089), and between A1AT levels and parasitic infection of any etiology ( p = 0.089), at 24-months of age. Significant associations between A1AT levels and wasting ( p = 0.006) and stunting ( p = 0.044) were found. Previous parasitic infections were not associated with fecal biomarkers at 24 months of age. To summarize, previous asymptomatic parasitic infections showed no association with intestinal barrier dysfunction. Notwithstanding, a tendency toward increased levels of the inflammatory biomarker was observed for current G. duodenalis and STH infections, and increased levels of the permeability biomarker were significantly associated with stunting and wasting.